PERUBAHAN SOSIAL DAN BUDAYA DALAM KEHIDUPAN MASYARAKAT PEDESAAN (Studi Pemanfaatan Teknologi Pertanian Kelompok Tani Sri Jaya 1 Kecamatan Air Nipis Kabupaten Bengkulu Selatan) - Boerman, Amrullah (JURNAL ILMIAH IDEA, 2024)
This research aims to determine the dimensions of social change that is occurring in the lives of rural communities due to the use of agricultural technology, and the impact of the use of agricultural technology on people's lives. In this case the author can understand the usefulness of the research results. Where theoretically it contributes thought to the development of sociological theories, especially functional structure theory, in the perspective of social and cultural changes in the lives of rural communities in the use of agricultural technology. To achieve this goal in this research the author used a qualitative approach, and in collecting research data used interview, observation and documentation techniques. The data collected has a level of trust so the researcher acts as the main instrument. Determining research subjects was carried out using a purposive technique, namely a technique for determining research subjects based on predetermined criteria. The results of this research suggest that the use of agricultural technology in the Sri Jaya 1 Farmers Group is grouped into several dimensions of change, namely in the structural dimension, the role of women farmers in agricultural pre-production has been replaced by technology. Then in the cultural dimension, there has been a change in the use of traditional and manual tools in harvesting rice, where previously farmers used ani-ani to harvest rice, now they have switched to using sickles and rice threshers which have been replaced by terser machines. Then the interactional dimension, the use of agricultural technology causes production costs to increase, so that farming communities look for alternative jobs outside the agricultural sector to cover the costs of producing crops using technology. Then, over time, interactions and close relationships between people are increasingly eroded by the busyness of farming communities who work continuously to cover the costs of agricultural production. The impact of agricultural technology is that the sense of togetherness and mutual cooperation between people begins to fade, and society becomes passive and has a materialistic and individualistic mindset.